Outbreak of hepatitis C virus infections originating from a breach in safe injection practices before contrast-enhanced computed tomography scanning. Issue 3 (November 2020) - Balmelli, C.; Merlani, G.; Martinetti, G.; Reinholz, D.; Paolucci, S.; Baldanti, F.; Piralla, A.; Del Grande, F.; Bernasconi, E.
Summary: Four patients who underwent contrast-enhanced computed tomography (CT) scanning were infected with hepatitis C virus from a contaminated multi-dose vial of NaCl. The outbreak likely occurred due to a breach in safe injection practices, resulting in contamination of the vial. Not all patients exposed to the same vial were infected. The uneven distribution of infections could be attributed to a stochastic effect of a low infectious dose. This implies that outbreak investigations need to be extended to all patients scheduled before and after the first identified infected patient to confirm or rule out nosocomial transmission.